National Land-based Climate Mitigation Scenarios Dataset - Tomoko Hasegawa; Shinichiro Fujimori; Kazuaki Tsuchiya; Akihiko Ito; Kiyoshi Takahashi (Scientific Data)
Abstract Given the need to reduce greenhouse gases emissions to meet the 2 °C or 1.5 °C target of the Paris Agreement, over 150 countries currently have net-zero targets. National inventories and projections of land-based emissions and mitigation strategies have not been well developed and remain limited compared to energy sectors. Here, we provide worldwide national land-based emission and mitigation scenario data with a detailed portfolio of mitigation options. This information contributes to filling the gap between integrated assessment model estimates and national greenhouse gas inventories for land-based emissions through estimation of carbon sequestration in managed forests. Second, these data can be used as a benchmark for countries developing national targets or strategies for agriculture, forestry, and other land use sectors as well as for reviewing national contributions in global assessments in a manner consistent with integrated assessment model estimates.